2009
DOI: 10.1177/104063870902100215
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Lymphoma and Pulmonary Filariasis in a Pet Domestic Rabbit (Oryctolagus Cuniculus Domesticus)

Abstract: Abstract. Spinal lymphoma and concurrent pulmonary filariasis are reported in a pet rabbit. The rabbit presented for pelvic limb paralysis resulting from extradural spinal lymphoma, presumably rising from the body of the sixth lumbar vertebra. The neoplasm was subsequently immunophenotyped as a B-cell lymphoma. Pulmonary filariasis was an incidental finding at necropsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Based on previous literature, our differential diagnosis included inflammatory infectious or neoplastic disorders, with degenerative disc disease being less likely. [1][2][3][4][5][12][13][14] MRI is considered the best imaging modality for investigating spinal diseases in humans and companion animals. In our rabbit, MRI correctly identified the cause of the neuro-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous literature, our differential diagnosis included inflammatory infectious or neoplastic disorders, with degenerative disc disease being less likely. [1][2][3][4][5][12][13][14] MRI is considered the best imaging modality for investigating spinal diseases in humans and companion animals. In our rabbit, MRI correctly identified the cause of the neuro-…”
Section: Discussionmentioning
confidence: 99%
“…Aetiologies of myelopathies reported in previous literature include vascular causes (ischaemic myelopathy), inflammatory causes (myelitis/meningomyelitis of unknown origin or infectious: Encephalitozoon cuniculi), 1 traumatic causes (fractures and vertebral subluxations) 2 and possibly metabolic causes as part of a wider range of central nervous system signs (lead and zinc intoxications). 3 Additionally, neoplastic causes such as lymphoma and adenocarcinoma 4,5 as well as degenerative causes, such as spondylosis of the lumbar spine and pathologies of the intervertebral disc, have been reported, with the highest prevalence for inflammatory, neoplastic and traumatic myelopathies.…”
Section: Introductionmentioning
confidence: 99%
“…For more specific identification, we performed PCR genotyping using DNA from tissue samples taken from the formalin-fixed uterus, but all PCR reactions were negative for Dirofilaria immitis, Dirofilaria repens, and Dipetalonema reconditum. We believe that our assay could have produced false negative results since DNA samples isolated from formalin-fixed tissue are often unsuitable for PCR analysis (Reed et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…18 Recent reports of lymphoma in rabbits also involved the cecum, spinal cord, and Harderian gland, where tumors were all B cell lymphomas. 14,19,26 Unlike multicentric lymphoma, cutaneous lymphoma is rarely diagnosed in rabbits in the United States. A recent 16year study of pet rabbits in the United States found that trichoblastomas were by far the most common cutaneous neoplasm, with collagenous hamartomas and leporipoxvirus-associated Shope fibromas being the next most frequent cutaneous tumors in pet rabbits.…”
mentioning
confidence: 99%
“…18 Recent reports of lymphoma in rabbits also involved the cecum, spinal cord, and Harderian gland, where tumors were all B cell lymphomas. 14,19,26…”
mentioning
confidence: 99%